Cutaneous melanoma: cost of illness under Brazilian health system perspectives - Cassia Rita Pereira da Veiga; Claudimar Pereira da Veiga; Alceu Souza; Alberto Julius Alves Wainstein; Andreia Cristina de Melo; Ana Paula Drummond-Lage (BMC, 2021)
Abstract Background The landscape of cutaneous melanoma (CM) diagnosis, staging, prognosis, and treatment has undergone fundamental changes in the past decade. While the benefits of new health resources are recognized, there is a distinct lack of accurate cost-of-illness information to aid healthcare decision makers. Methods The cost-of-illness study for CM was conducted from the perspective of two health systems in Brazil: the public health system (Unified Health System, SUS) and the private health system (Health Management Organization, HMO). The study considered the direct medical cost in a bottom-up analysis, using melanoma incidence, knowledge of the disease's progression, and the overall survival rates. The executional costs for the complete healthcare delivery cycle were investigated considering different disease stages and possible clinical course variations. The structural cost was assessed qualitatively considering the health value chain in Brazil. Results CM represents a critical financial burden in Brazil, and the cost of illness varied according to the health system and by stage at diagnosis. HMO patient costs are approximately 10-fold and 90-fold more than a SUS patient in the early-stage and advanced disease, respectively. Overall, spending on advanced disease patients can be up to 34-fold (SUS) or 270-fold (HMO) higher than that required for the early-stage disease. Given the massive amount of resources spent by the SUS and HMO, significant efforts must be made to improve the health value chain to deliver the right mix of medical care goods and services using available resources. Conclusion The cost-of-illness study for CM has the potential to inform policymakers and decision-makers regarding the economic burden that melanoma impose on a society in terms of the use of health care services, assisting them in making projections of future health care costs and resource allocation decisions. We believe that cost-of-illness analysis from a strategic perspective could be of help in assessing executional costs and be used to support the change in structural costs required for long-term strategies related to the health value chain.